Pengaruh Model Pembelajaran Berbasis Masalah dengan Strategi Rotating Trio Exchange Terhadap Hasil Belajar Fisika Peserta Didik Kelas XI SMAN 1 Lingsar Tahun Ajaran 2017/2018 - Wina Mustika; Susilawati Susilawati; I Wayan Gunada (Department of Physics Education, Universitas Mataram, 2018)
This study aims to understand the influence of a problem based learning model using rotating trio exchange strategy (RTE) towards students physics learning achievement of year XI MIA SMAN 1 Lingsar. This study is quasi experiment with Non-equivalent control group design. The population of this study was the whole students of year XI MIA SMAN 1 Lingsar of the academic year 2017/2018 whose total is 89 students. The sampling technique of the study was purposive sampling, which in turn, year XI MIA 1 treated as experimental class and year XI MIA 2 as the control class. The instrument used was a multiple choice test and observation. The multiple choice refers to the cognitive ability of the students (C1C6) which was 35 items in total which has been tested for validity, reliability, appropriateness, and the level of its difficulty have been examined. Evaluate studentsÃ¢â¬â¢ affective and psychomotoric assessments using observation sheets. Based on the result of the study it was gained that students average score of pre-test of both experimental and control class was 42 and 23, while the average score of post-test of both experimental and controlled class was 70 and 67 subsequently. The data gained has been previously examined its normality and homogeneity. It was obtained that experimental and control class was distributed normally and homogeneous. The hypothesis was examined using statistical analysis, i.e. parametric t-test polled variant with t test of both sides. It is obtained that dan diperoleh ÃÂ and ÃÂ on the level of significant 5%. The value ofÃÂ ÃÂ ÃÂ , then ÃÂ is rejected and ÃÂ is accepted. The result indicated that there was positive influence of a problem based model using rotating trio exchange (RTE) strategy towards the students achievement on physics in year XI MIA of SMAN 1 Lingsar